Effect of pe-cooling treatment, 1-methylcyclopropene (1-MCP) and controlled atmosphere (CA) on vase life of cut spray carnation flowers - Burana, Chairat (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2019)
The vase life of ‘Light Pink Barbara’ (LPB) and ‘Boundee’ (BD) after treatment with pre-cooling at 5°C for 48 h (dark condition), 1-MCP treatment by EthylBloc® (EB) sachet for 6 h and CA (CO2 20% and O2 5% at 5°C for 12, 24 and 48 h) has been investigated. All treatments decreased ethylene production in both cultivars ‘LPB’ and ‘BD’. Pre-cooling treatment prolonged the vase life of ‘LPB’ but induced senescence in ‘BD’. The vase life of both cut spray carnations were prolonging after by 1-MCP treatment in the form of EB. CA treatments prolonged the vase life of ‘LPB’ cut single carnation flowers while decreased vase life of ‘BD’. The vase life of multiple flowers on a stem of ‘LPB’ was prolonged by pre-cooling, 1-MCP and CA for 12 h treatments. Treatments with CA for 24 h and 48 h enhanced the senescence in ‘LPB’. The vase life of multiple flowers on a stem of ‘BD’ prolonged by 1-MCP treatment, but reduced by pre-cooling and all CA treatments. These finding suggest that CA treatment was useful to prolong the vase life and maintain the quality of ‘LPB’ during transportation and display.